Pulse height distribution of signals produced by exposing a thin GEM chamber to beta rays from an Sr-90 source - Ahn, B. J.; Ha, Y. J.; Hahn, C. H.; Park, S. T.; Yi, C-Y; Lee, Rena (Journal of the Korean Physical Society, 2014)
Researchers at Changwon National University’s Radiation Detector Development Laboratory(RDD) fabricated a single-channel double-GEM(gas electron multiplier) chamber and measured the pulse height distribution of signals produced by exposing the chamber to an Sr-90 source provided by the Korea Research Institute of Standards and Science(KRISS). A beta-ray electron incident on the GEM chamber ionizes gaseous molecules in the drift region of the chamber by means of electromagnetic interactions. After the leased electrons are amplified by electron avalanches in the GEM stages, the multiplied electrons go from the lowest GEM foil toward the anode of the chamber and induce one signal pulse, corresponding to the incident electron, on the readout pad. The charge signal distribution measured during Sr-90 radioactive source irradiation was compared with the simulation done by using a Landau probability distribution. The energy loss distribution of beta-ray electrons, which deposited part of their energy in a thin GEM chamber while traversing gases within the drift region of that chamber, was in good agreement with the calculation of the Landau probability distribution. The pulse height distributions for energy losses of beta-ray electrons incident on the chamber due to Sr-90 disintegrations were observed in order to select a suitable gas mixture for the chamber. The ratios of the Ar/CO 2 gas were 75/25, 80/20, 85/15, and 90/10.